Design and Implementation of Motion Expression Activity Program Applying LMA to Children with Intellectual Disabilities Using ICT - Hong, SungHee; Hye Kim, Eun (International Journal of Engineering and Technology, 2018)
The purpose of this study is to design and implement a movement expression activity program through ICT using Laban's LMA in recognizing movements of children with intellectual disabilities. Kinect and Laban's movements were used to construct a motion expression activity program. In this research method, screen image screen and theme music were used as contents of musical work <Les Miserable>. The motions of randomly set to 40 kinds, and when the movement of the screen coincided with each other, the score was displayed with the ringing tone. The experimental design was conducted for 13 children with disabilities for 4 days (12. 21 12. 25. 2016). In addition the willingness to match the motion of the screen in kinetic expression activities using Kinect, repetitive exercises gradually improved the completeness of the movements and the final score of the game. This study, it has been observed that curiosity, interest, and immersion in movement expression activity are designed and implemented by using Kinect for the movement expression activity program with a new education game approach that can eliminate the fear of physical activity it was tried.Â